ВИВЧЕННЯ ГОСТРОЇ ТОКСИЧНОСТІ НАНОХРОМУ ЦИТРАТУ ПРИ РІЗНИХ ШЛЯХАХ ВВЕДЕННЯ - Sadohurska К. V. (Фармацевтичний часопис, 2016)
ANALYSIS OF ACUTE TOXICITY OF NANOCHROMIUM CITRATE IN CASE OF DIFFERENT WAYS OF ADMINISTRATION К.V. Sadogurska Higher State Educational Establishment of Ukraine “Bukovinian State Medical University”, Chernivtsi Introduction. In recent years advanced nanotechnologies have rapidly developed both in Ukraine and the whole world – these are technologies of a directed obtaining and use of substances and materials in the range of nanoparticles size from 0,1 to 100 nanometers. The interest to nanobiology, nanomedicine, nanopharmacology and nanopharmacy has been constantly increasing. Perspective structures to be used in nanomedicine are nanoparticles of metals such as silver, copper, iron, gold tec. Onrush of nanotechnologies and obtaining nanomaterials stipulates the necessity to examine their safety to avoid possible unfavourable consequences both for the health of population and environment. Our attention is drawn to nanochromium citrate, an organic compound of chromium obtained at the Ukrainian State Scientific-Research Institute of Nanobiotechnologies and Resource-Saving. Chromium as a trace element is known to play an important role in carbohydrate metabolism, and due to the regulation of insulin production and metabolism it helps to maintain a normal glucose level in the blood. Due to the fact that biological activity and safety of nanochromium citrate has not been completely examined today, the objective of our work is to study acute toxicity of nanochromium citrate in animals in case of different ways of administration. Investigation methods. Acute toxicity of nanochromium citrate (NCC) was examined by means of express-method to detect mean effective dose and its error. Acute toxicity was studied against the ground of a single enteral (into the stomach) and parenteral administration. Acute toxicity of NCC in the concentration of 200 mg/l (Ltd «Nanomaterials and nanotechnologies», Kyiv). After NCC solution was injected the animals were observed during 14 days. Attention was drawn to their appearance, behavior, condition of hair, attitude to food, rhythm and frequency of respiration, time of occurrence and signs of intoxication, its severity, course, time of death of the animals. Results and discussion. Therefore, the manifestation of acute intoxication of rats with NCC is characterized by the signs of its direct affect on the CNS. The cause of death of the animals might be inhibition of vitally important centers in the brain. Expressiveness and time of occurring the signs of NCC intoxication depends on the dose and way of administration into the body. The lowest toxicity of the compound is observed with enteral way of administration. By DL50 indices toxicity increases in the following succession: intragastric<intraperitoneal<intravenous. In case of intraperitoneal administration toxicity increases by 14,5 times, intravenous – practically by 40 times as compared to the intragastric administration. Assuming DL50 of NCC in case of intravenous administration as 1, this index in case of intraperitoneal administration is 2,74, and with intravenous injecting it is 39,9. On the basis of the results obtained according to the toxicologic classification of H.C. Hodge, L.H. Sterner by the value of DL50 index, in case of enteral way of administration into the body (65 mg/kg) NCC can be classified as belonging to the III class (moderate-toxic substances), and in case of parenteral way of administration (intravenous, intraperitoneal) – to the II class (high-toxic substances), as DL50 index is within the limits of 1,63-4,47 mg/kg - by К.К. Sydorov. Detected parameters of acute toxicity of NCC may be used in the study of toxic characteristics during long administration as well as will help to determine doses while conducting screening examinations of predictable biological properties of the compound. Conclusions. 1. Expressiveness and time of occurring of acute intoxication with nanochromium citrate depend on the dose and ways of its administration into the body. By the indices of DL50 toxicity increases in the following succession: intragastric<intraperitoneal<intravenous. 2. According to toxicological classification of substances nanochromium citrate belongs the III class of toxicity (moderate-toxic substances), and in case of parenteral way of administration (intravenous, intraperitoneal) – to the II class (high-toxic substances). References 1. Berezovskaya Y.V. Klassyfykatsyya khymycheskykh veshchestv po parametram ostroy toksychnosty pry parenteralʹnykh sposobakh vvedenyya / Y.V. Berezovskaya // Khymyko-farmatsevtycheskyy zhurnal. - 2003. - T. 37, № 3. - S. 32-34. 2. Dmytrukha N.M. Kharakterystyka imunotoksychnoyi diyi spoluk svyntsyu z mikro- ta nanochastynkamy / N.M. Dmytrukha, S.P. Luhovsʹkyy, O.S. Lahutina // Suchasni problemy toksykolohiyi, kharchovoyi ta khimichnoyi bezpeky. - 2014. - № 1,2. - S. 59-66. 3. Doklinichni doslidzhennya likarsʹkykh zasobiv (metodychni rekomendatsiyi) / za red. O.V. Stefanova. - K.: Avitsena, 2001. - 528 s. 4. Mykroélementozy cheloveka / A.P. Avtsyn, A.A. Zhavoronkov, M.A. Rash [y dr.]. - M.: Medytsyna, 1991. - 496 s. 5. Nanomaterialy v biolohiyi. Osnovy nanoveterynariyi / V.B. Borysevych, V.H. Kaplunenko, M.V. Kosinov. - K.: Avitsena, 2010. - 416 s. 6. Nanonauka, nanobiolohiya, nanofarmatsiya / I.S. Chekman, Z.N. Ulʹberh, V.O. Malanchuk [ta in.]. - K.: Polihraf plyus, 2012. - 328 s. 7. Pat. 49050 A Ukrayina. C07C 51/41. Sposib Kaplunenka- Kosinova otrymannya karboksylativ z vykorystannyam nanotekhnolohiyi / Kosinov M.V., Kaplunenko V.H.; opubl. 12.04.2010, byul. № 7. 8. Prozorovskyy V.B. Ékspress-metod opredelenyya sredney éffektyvnoy dozy y ee oshybky / V.B. Prozorovskyy, M.P. Prozorovskaya, M.V. Demchenko // Farmakolohyya y toksykolohyya. – 1978. - № 4. S. 497-502. 9. Sydorov K.K. O klassyfykatsyy toksychnosty yadov pry parenteralʹnykh sposobakh vvedenyya / K.K. Sydorov // Toksykol. novykh promyshlennykh khymycheskykh veshchestv. – 1973. - № 13. S. 47-51. 10. Chekman I.S. Nanofarmakolohiya / I.S. Chekman. - K.: Zadruha, 2011. - 424 s. 11. Anderson R.A. Chromium, glucose intolerance and diabetes / R.A Anderson // J Am. Coll. Nutr. - 1998. - Vol. 17, № 6. - R. 548-555. 12. Hodge H.C. Tabulation of toxicity classes / H.C. Hodge, L.H. Sterner // Am. Industr. Hyg. Ass. Quart. - 1943. - Vol. 10, № 4. - R. 93. 13. Sengupta J. Physiologically important metal nanoparticles and their toxicity / J. Sengupta, S. Ghosh, P. Datta, A. Gomes // J. Nanosci Nanotechnol. - 2014. - Vol. 14, № 1. - R. 990-1006. 14. Yohan D. Applications of nanoparticles in nanomedicine / D. Yohan, V. Chithrani // J. Biomed Nanotechnol. - 2014. - Vol. 10, № 9. - P. 2371-2392.